The relevance of Jan Patocka’s phenomenology in questions of science and religion - Ortega Rodríguez, Iván (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Jan Patocka’s attempt of an «a-subjective» phenomenology represents a complex thesis which has in itself many potentialities of which Patocka himself was not probably aware. In this article we enumerate some problems to which Patocka’s thought can give us a new insight. Firstly we make a brief description of the fundamental of his «a-subjective» phenomenology. Secondly and finally, we indicate four problems concerning science and religion to which Patocka’s theses are relevant. These problems are the epistemic value of scientific research, the mind-body problem, the possibility of a religious revelation and the reasonability of theism and atheism. In some of these problems we indicate references to authors who have already dealt with the topic for further information. Our aim is to invite scholars to take into account the thought of Jan Patocka, so that they will deepen in the questions we present here.